ChemInform Abstract: Lawsone in Organic Synthesis. Issue 42 (October 2015) - Jordao, Alessandro K.; Vargas, Maria D.; Pinto, Angelo C.; da Silva, Fernando de C.; Ferreira, Vitor F.
Abstract Review: 326 refs.